Genetic diversity analysis of indigenous and exotic germplasm of barley (Hordeum vulgare L.) and identification of trait specific superior accessions - Kaur, Vikender; Kumari, Jyoti; ., Manju; Jacob, Sherry R; Panwar, Bhopal Singh (Journal of Cereal Research, 2018)
Barley is an important feed, food, malt and brew purpose crop in India. The new challenges for production in the era of climate change envisage involvement of diverse germplasm for further exploitation in breeding. Genotypic variation in 256 indigenous and exotic barley germplasm accessions was evaluated for nine quantitative and seven qualitative traits during two consecutive cropping years (2014–15 and 2015–16). Indigenous collections were assembled from seven different states of India representing four agro-ecological zones while exotic material comprised of 80 accessions from USA and Syria. The coefficient of variation ranged from 3.47–41.21% in Indian accessions to a little bit higher (3.34–56.14%) in exotic germplasm suggesting exotic accessions were more diversity. The principal component analysis showed that four most informative components could describe 72.22% of the total multivariate variance and cluster analysis divided all accessions into four clusters showing an association between genetic diversity and geographical diversity. Spike and grain traits were contributing more to variability among the accessions and lesser to peduncle length, plant height and days to maturity. Further superior accessions namely IC0364040 (tall landrace with more grains/spike), IC0036966 (early maturing), IC0041585 (tall, high yield), IC0398681 (long spikes, tall), hull-less exotic landraces EC0362267 (more spike triplets/spike, short plant height) and EC0481703 (long spike, high yield, two-rowed) were identified and than be utilization as donors in breeding programs for different agro-ecologies. Doi.org/ 10.25174/2249-4065/2018/83620